Strong short-range interactions in one-dimensional proton conductor - Stasyuk, I.V.; Vorobyov, O. (Condensed Matter Physics, 2003)
The behaviour of one-dimensional proton conductor is investigated on the basis of orientational-tunnelling model. The previously proposed technique which permits the proton interactions to be taken into account in the zeroorder Hamiltonian, and is based on Green’s function’s expansion in terms of irreducible Green’s function parts, is generalized. The Larkin equation for the one-particle proton Green’s function is solved, while irreducible Larkin part is calculated within the framework of the first order approximation. The proton energy spectrum and chemical potential behaviour are investigated, and the results are compared with the ones previously obtained in the Hubbard-1 type approximation.